Information Retrieval Technology Second Asia Information Retrieval Symposium, AIRS 2005, Jeju Island, Korea, October 13-15, 2005, Proceedings - Yamada, Akio; Meng, Helen; Myaeng, Sung Hyon (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2005)
Asia Information Retrieval Symposium (AIRS) was established in 2004 by the Asian information retrieval community after the successful series of Information Retrieval with Asian Languages (IRAL) workshops held in six different locations in Asia, starting from 1996. The AIRS symposium aims to bring together international researchers and developers to exchange new ideas and the latest results in the field of information retrieval (IR). The scope of the symposium covers applications, systems, technologies and theoretical aspects of information retrieval in text, audio, image, video and multi-media data. We are very pleased to report that we saw a sharp and steady increase in the number of submissions and their qualities, compared with previous IRAL workshop series. We received 136 submissions from all over the world including Asia, North America, Europe, Australia, and even Africa, from which 32 papers (23%) were presented in oral sessions and 36 papers in poster sessions (26%). We also held a special session called "Digital Photo Albuming," where 4 oral papers and 3 posters were presented. It was a great challenge and hard work for the program committee to select the best among the excellent papers. The high acceptance rates witness the success and stability of the AIRS series. All the papers and posters are included in this LNCS (Lecture Notes in Computer Science) proceedings volume, which is S- indexed. The technical program included two keynote talks by Prof. Walter Bender and Prof.